2017
DOI: 10.1186/s40643-017-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptional response of Aspergillus niger in the process of glucoamylase fermentation

Abstract: Background: In the phase of oxygen limitation during Aspergillus niger fermentation, the cell growth decreased, while the yield of glucoamylase increased continuously and significantly. Explanation on the changes of transcriptome profile during this process may improve our understanding on mechanisms of cell adaption and enzyme production in A. niger. Results:The transcriptomic data from 4 time points in oxygen limitation process of a glucoamylase production A. niger strain were analyzed. Hierarchical clusteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Figure 5 and Additional file 1 : Table S5 summarize the amino acid pools in all three overexpression strains compared to B36. In general, Ala, Glu, Gly, Leu, and Lys are the top five amino acids in the biomass of A. niger , whereas Ser, Thr, Ala, Leu, and Gly account for about 50% of the total amino acids in GlaA [ 40 ]. Our metabolomics analyses uncovered that in all four strains, amino acids from the glutamate family are most and aromatic amino acids are least abundant, which is in general agreement to previously reported amino acid pools in A. niger [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 and Additional file 1 : Table S5 summarize the amino acid pools in all three overexpression strains compared to B36. In general, Ala, Glu, Gly, Leu, and Lys are the top five amino acids in the biomass of A. niger , whereas Ser, Thr, Ala, Leu, and Gly account for about 50% of the total amino acids in GlaA [ 40 ]. Our metabolomics analyses uncovered that in all four strains, amino acids from the glutamate family are most and aromatic amino acids are least abundant, which is in general agreement to previously reported amino acid pools in A. niger [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous transcriptome analysis of oxygen-limited fermentation for glucoamylase production in A. niger [ 13 ], 5 genes, related to fatty acids degradation and continuously up-regulated during oxygen-limitation period, were selected as candidate genes (Table 2 ). Five genes named fadE (encoding Acyl-CoA dehydrogenase), fadA (encoding Acetyl-CoA C-acyltransferase), hyp (encoding hypothetical protein with hydrolase activity), cyp (encoding cytochrome P450 monooxygenase), acy (encoding acyltransferases) were overexpressed in the pyrG locus of A. niger YS20.2 genome under the control of Tet-on system (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, multi-omics integrative analysis of glucoamylase fermentation process in A. niger in our lab [ 13 ] showed that fatty acids degradation and precursor amino acids synthesis were elevated under oxygen limitation, whereas fatty acid synthesis was diminished. While it is well known that lipids, as essential components of cell membranes, play an important role in many processes such as cell signaling, energy supply and cell growth [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table S5 summarize the amino acid pools in all three overexpression strains compared to B36. In general, Ala, Glu, Gly, Leu, and Lys are the top five amino acids in the biomass of A. niger, whereas Ser, Thr, Ala, Leu, and Gly account for about 50% of the total amino acids in GlaA [40]. Our metabolomics analyses uncovered that in all four strains, amino acids from the glutamate family are most and aromatic amino acids are least abundant, which is in general agreement to previously reported amino acid pools in A. niger [41].…”
Section: Metabolic Differences Revealed By Multivariate Statistical Amentioning
confidence: 99%